Prolonged shedding of severe acute respiratory syndrome coronavirus 2 in patients with COVID-19. Issue 1 (1st January 2020) - Li, Qian; Zheng, Xiao-Shuang; Shen, Xu-Rui; Si, Hao-Rui; Wang, Xi; Wang, Qi; Li, Bei; Zhang, Wei; Zhu, Yan; Jiang, Ren-Di; Zhao, Kai; Wang, Hui; et al.
ABSTRACT: Following acute infection, individuals COVID-19 may still shed SARS-CoV-2 RNA. However, limited information is available regarding the active shedding period or whether infectious virus is also shed. Here, we monitored the clinical characteristics and virological features of 38 patients with COVID-19 (long-term carriers) who recovered from the acute disease, but still shed viral RNA for over 3 months. The median carrying history of the long-term carriers was 92 days after the first admission, and the longest carrying history was 118 days. Negative-positive viral RNA-shedding fluctuations were observed. Long-term carriers were mostly elderly people with a history of mild infection. Infectious SARS-CoV-2 was isolated from the sputum, where high level viral RNA was found. All nine full-length genomes of samples obtained in March–April 2020 matched early viral clades circulating in January–February 2020, suggesting that these patients persistently carried SARS-CoV-2 and were not re-infected. IgM and IgG antibodies and neutralizing-antibody proﬁles were similar between long-term carriers and recovered patients with similar disease courses. In summary, although patients with COVID-19 generated neutralizing antibodies, they may still shed infectious SARS-CoV-2 for over 3 months. These data imply that patients should be monitored after discharge to control future outbreaks.